Molecular characterization of hepatitis B virus genotypes A and D among inmates and blood donors in Northeastern Kenya - Vincent Bahati Odallo; Okoti P. Aluora; Wallace Bulimo; George Gachara (PLoS ONE, 2026)
Introduction Hepatitis B virus (HBV) persists as a major global public health burden, with hyperendemic prevalence in sub-Saharan Africa. Populations with elevated exposure to percutaneous transmission risks, including incarcerated individuals and healthcare workers demonstrate heightened HBV susceptibility. Despite this, genomic data from Northeastern Kenya and Kenyan prison populations remain scarce. Objective To characterize HBV genotypic diversity circulating in Northeastern Kenya, among low-risk (blood donors) and high-risk (prison inmates) populations. Methods A cross-sectional investigation compared HBV seroprevalence and genotypes between incarcerated individuals (n = 130) and voluntary blood donors (n = 130) in Garissa County, Northeastern Kenya. Serum samples were subjected to Hepatitis B surface antigen (HBsAg) screening, PCR amplification of a 940-bp overlapping surface/polymerase gene, sequencing, and phylogenetic/recombination analyses of the resulting sequences. Results Seroprevalence was higher among incarcerated individuals (5.4%, 7/130) than blood donors (3.1%, 4/130). Hepatitis B Virus DNA was detected in 22 samples which were all successfully sequenced. Genotype D dominated both cohorts (81.8%), while genotype A sub genotype A1 occurred exclusively in incarcerated participants (18.2%). All genotype D strains were recombinants: D/A (61%) and D/E (39%). Sequences are accessible in GenBank (accession numbers: PV816552–PV816573). Conclusions This first genomic study of HBV in Kenyan prisons confirms incarcerated populations as high-risk. The predominance of genotype D—an unusual finding in this region and high recombinant frequency (100% of genotype D strains) underscore significant viral evolution. Expanded genomic surveillance is imperative to define HBV diversity, inform vaccine efficacy monitoring, guide screening policies and optimize control strategies in Northeastern Kenya.